A retrospective study on the prevalence and genetic characteristics of porcine parvovirus 6 in Guangxi, China - Cao, Liang; Ji, Chenxi; Yu, Ziping; Wang, Wei; Kang, Lulu; Jin, Lin; Han, Zaiyong; Nan, Fulong; Li, Wenjie; Xin, Jialiang (Frontiers in Microbiology, 2026)
Porcine parvovirus 6 (PPV6) is an emerging virus whose epidemiology and clinical significance in China remain poorly defined. This study investigated the prevalence and genetic characteristics of PPV6 in Guangxi Province, China, using 497 porcine serum samples collected between 2015 and 2019. The overall PPV6 prevalence was 12.5% (62/497), with regional rates ranging from 12.0 to 17.6%. A high frequency of co-infection with porcine circoviruses (PCVs) was detected, with 46.8, 19.4, and 3.2% of PPV6-positive samples were also positive for PCV2, PCV3, and PCV4, respectively. To the best of our knowledge, this study describes the first reported detection of PPV6 and PCV4 co-infection. Ten complete PPV6 genomes were successfully sequenced and grouped into two sizes, 6,112 and 6,111 nt, the latter resulting from a single thymine deletion in the 3’ untranslated region (UTR). Phylogenetic analysis based on VP1 sequences classified global PPV6 strains into two distinct lineages (A and B). All strains identified in this study clustered within Group B. Conversely, three previously reported Chinese strains belonged to Group A. Fourteen amino acid substitutions in VP1 were strongly associated with this phylogenetic separation. Selection pressure analysis further identified multiple positively selected sites within the capsid protein. Overall, these findings advance understanding of the molecular epidemiology of PPV6 in southern China and highlight its potential interaction with PCVs, providing a basis for future investigations into viral pathogenesis and vaccine development.